1985
DOI: 10.1210/jcem-61-5-807
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Plasma Free Fatty Acid Concentrations in Noninsulin-Dependent Diabetes Mellitus: Evidence for Insulin Resistance*

Abstract: Plasma glucose, insulin, and FFA concentrations were determined in 15 normal subjects and 15 patients with noninsulin-dependent diabetes mellitus (NIDDM) from 0800 to 1600 h. Breakfast and lunch were consumed at 0800 and 1200 h, respectively, and plasma concentrations were measured at hourly intervals from 0800-1600 h. Plasma glucose concentrations between 0800 and 1600 h were significantly elevated in patients with NIDDM, and the higher the fasting glucose level, the greater the postprandial hyperglycemia. Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
100
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(108 citation statements)
references
References 16 publications
6
100
0
2
Order By: Relevance
“…Effects of FFAs and glycerol on splanchnic glucose uptake. Plasma FFAs are commonly elevated in a variety of disease states, including type 2 diabetes and obesity (1,5,6,55). After the observation by Randle et al (8) that increased FFAs decreased insulin-stimulated glucose uptake in perfused hearts, a number of studies have shown that they can also decrease either leg (and therefore presumably skeletal muscle) or whole-body glucose uptake in humans (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of FFAs and glycerol on splanchnic glucose uptake. Plasma FFAs are commonly elevated in a variety of disease states, including type 2 diabetes and obesity (1,5,6,55). After the observation by Randle et al (8) that increased FFAs decreased insulin-stimulated glucose uptake in perfused hearts, a number of studies have shown that they can also decrease either leg (and therefore presumably skeletal muscle) or whole-body glucose uptake in humans (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of abnormal fat metabolism to these defects is an area of active investigation. People with type 2 diabetes commonly have elevated FFA and glycerol concentrations (1,5,6). Although it is well established that FFAs can blunt the response of muscle to insulin (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), elevated FFAs have been reported to increase (20), decrease (21), or have no effect (22,23) on initial splanchnic glucose extraction.…”
mentioning
confidence: 99%
“…The adipose tissue of obese persons releases more NEFAs into the circulation, and subjects with type 2 diabetes have high NEFA concentrations. 8,9 A high plasma NEFA concentration is a risk factor for deterioration of glucose tolerance independent of the other insulin resistance or insulin secretion markers that characterize subjects at risk for type 2 diabetes. 10 Day-long elevations in plasma NEFA levels can lead to aggravation of impaired glucose homeostasis in obese and type 2 diabetes individuals.…”
Section: Obesity Nefas and The Pathogenesis Of Type 2 Diabetes Mellmentioning
confidence: 99%
“…Furthermore, obesity and insulin resistance are found in people who are at an increased risk for developing these disorders, suggesting that they could be common pathological factors, or at least early events in their development. Second, obesity and Type 2 diabetes are often associated with hypertriglyceridaemia or increased circulating concentrations of NEFA [2,3]. Therefore Type 2 diabetes can also be considered a lipid disorder as well as a disease of glucose tolerance [4] and it is possible that increased circulating lipid concentrations explain, at least in part, not only insulin resistance but also betacell dysfunction in Type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%